DEVELOPMENT MODEL OF PATISSERIE PROJECT-BASED LEARNING - Ana, Ana; Nurlaela, Lutfhiyah (Journal of Technical Education and Training, 2012)
ï»¿The study aims to find a model of patisserie project-based learning with production approach that can improve effectiveness of patisserie learning. Delphi Technique, Cohen's Kappa and percentages of agreements were used to assess model of patisserie project based learning. Data collection techniques employed in the study were questionnaire, check list worksheet, observation, and interview sheets. Subjects were 13 lectures of expertise food and nutrition and 91 students of Food and Nutrition Program from UPI, UNY, UNESA and UM. The results shows that model of patisserie project based learning with production approach can be used in patisserie learning, with a fairly high level of agreement, which is 0.78 average Cohen's Kappa coefficient. The model was implemented very well, as shown by 94.77% average implementation. Thus, model of patisserie project based learning with production approach can be used to improve the quality of patisserie learning. The results shows that model of patisserie project based learning with production approach can be used in patisserie learning with a fairly high level of agreement in 0.78 average Cohen's Kappa coefficient. The model was implemented very well, as shown by 94.77% average implementation. Thus, model of patisserie project based learning with production approach can be used to improve the quality of patisserie learning.